Improving Students’ Vocabulary Mastery by Using Realia at The Fourth Semester of Midwife Program - Deviga, Lidia; Ardhani, Radian Arum (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2024)
This study of the research is aims to find out: 1) the improvement of the students’ vocabulary mastery by using realia at the fourth semester of midwife program in STIKES Bhakti Husada Mulia Madiun. 2) the effect of teaching learning process when the teaching vocabulary by using realia. The researcher conducted a classroom action research from march to may at the fourth semester of midwife program. The subject of the research of the fourth semester midwife program that consist of 31 students. researcher using four English skill, mainly: planning, implementing, observing and reflecting. The data was analyzed in qualitative and quantitative method. The qualitative data were obtained from observation sheet, While the quantitative data from the result of vocabulary test. it was carried out in two cycle and each cycle was carried out in one meeting. The researcher makes four steps. There are: planning, implementing, observing and reflecting. The instrument used were the vocabulary test, and observation. The finding indicated that using realia could improve the student’s vocabulary mastery. in the preliminary study there were 0% out of 31 students got scores 75, as the criteria of success. In the first cycle the score increased : there were 18 ( 58,1%) out of 31 students got scores equal 75 up to 100 and the second cycle ,there were 27 ( 87,09%) out of 31 students were active in teaching and learning process. And get score 75 up to 100. The scores had fulfilled the criteria of success that is 75. Besides that, there were good effect in the teaching and learning process. Such as the students more active in following the teaching and learning process using realia it also improved student’s participant in learning vocabulary and the students could focus more on the lesson.